Genetic resources and fodder quality in sesbania - Tothill, J.C.; Reed, J.D.; Tsehay, A. (Nitrogen Fixing Tree Association, 1990)
The International Livestock Centre for Africa has a genetic base of 300 accessions from 20 species of Sesbania. The largest number of these are represented by the perennials S. sesban (207), S. goetzii (18), and S. keniensis (8) and the short-lived perennial S. macrantha (97). Almost all of this collection is under evaluation in Ethiopia at Debre Zeit (1850 m altitude, 850 mm rainfall) and at Addis Ababa (2380 m altitude, 1100 mm rainfall), both on seasonally waterlogged Vertisols. There is considerable variation both within and between accessions of S. sesban in vigour of growth, growth form, dry season survival, growth response to cutting, stem color, tannins, and related polyphenolic compounds, and possibly nematode resistance and beetle (Mesoplatys ochroptera) attack. Over a wide range of accessions N contents have been found to range from 2.6 to 4.0 percent. Sheep fed S. sesban grew at 50 g/day which equalled the best legume hay (Vicia dasycarpa), which was twice that from equivalent levels of natural multi-purpose trees (MPTs), e.g., Acacia seyal.